Cape Verde : Second Review Under the Policy Support Instrument; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the Second Review under the Policy Support Instrument (PSI) of Cape Verde discusses the macroeconomic framework and recent developments. Cape Verde's economic program under the PSI is designed to help the country prepare for the opportunities and challenges associated with its graduation from the United Nations least-developed-country (LDC) status in 2008. IMF staff recommended, and the authorities agreed, that a comprehensive medium-term investment plan be prepared, including for state-owned enterprises. This approach would support prioritization of public investment and the planning needed to secure concessional external financing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet